Mortuary Rites for Inanimate Objects: The Case of Hari Kuyō - Kretschmer, Angelika (Japanese journal of religious studies, 2000)
In Japan, as in other industrialized countries, old and broken objects mostly end up in the trash. Some items, however, end their "lives" with a special ritual. This article is the first serious Western-language treatment of mortuary rites (kuyō) for inanimate objects. The history of these rites, the Buddhist and Shinto justifications for them, and the motivations of the participants in them are among the topics about which little is known. In an attempt to enhance our knowledge of kuyo, this article examines mortuary rites for needles-objects which are emblematic of women. The goddess connected to the rites is introduced, and mortuary rites for needles performed today at three locations in Tokyo are described.